(untitled) - Campbell, Mary K. (New York, 2018)
n addition, the book's revised state-of-the-art visual program improves learning outcomes and its innovative magazine articles, "Hot Topics in Biochemistry" now reflect the latest advances in the field. Count on BIOCHEMISTRY, 9th Edition, to lead the way in currency, clarity, and innovation for your one-semester biochemistry course
Keywords: Biochemistry,Hóa sinh